Corpus analysis of conjunctions: Arabic learners' difficulties with collocations - Hassan, Haslina; Hizbullah, Nur; Arifa, Zakiyah (Penerbit Universiti Sultan Zainal Abidin, 2023)
This paper examines Arabic majors use of conjunctions in their essays both in the application (qualitative) and frequency of conjunctions used (quantitative). The essays serve as a corpus for this study where conjunctive use and misuse among learners of Arabic are described and how certain combinations of words are preferred. Sketch Engine was employed to track the frequency of conjunctions used and to identify the concordance lines of Arabic conjunctions and the collocates. A simple frequency counts reveals that out of more than 83 conjunctions available in Arabic, only 48 were used and the rest 35 were not employed at all by the students. However, the use was not necessarily correct. There seemed to be a confusion in the application of these conjunctions, particularly those which carry similar meanings with the ones in L1. Another problem with its usage lies in the use of collocations; where translation of L1 was applied to the Arabic conjunctions. Mother tongue interference could be the reason for the confusion since direct translation of the word can be used in the same context, but the contexts of their applications are different. This study highlights the need to focus on these errors when teaching Arabic to second or foreign language learners